1964
DOI: 10.1128/jb.88.6.1688-1694.1964
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Yeast Carotenoids

Abstract: The biosynthesis of carotenoids was followed in Rhodotorula glutinis and in a new strain, 62-506. The treatment of the growing cultures by methylheptenone, or ionone, vapors permitted observations of the intermediates in the biosynthetic pathway. On the basis of concentration changes and accumulation in blocked pathways, the sequence of carotenoid formation is postulated as phytoene, phytofluene, i-carotene, neurosporene, ,B-zeacarotene, y-carotene, torulin, a C40 aldehyde, and torularhodin. Torulin and torula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
11

Year Published

1971
1971
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 23 publications
1
30
0
11
Order By: Relevance
“… BIOSYNTHETIC PATHWAY OF CAROTENOID PRODUCTION IN RHODOTORULA GLUTINIS Adapted from Simpson et al. (1964), Bonaly and Malenge (1968) and Hayman et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… BIOSYNTHETIC PATHWAY OF CAROTENOID PRODUCTION IN RHODOTORULA GLUTINIS Adapted from Simpson et al. (1964), Bonaly and Malenge (1968) and Hayman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Carotenogenesis in Rhodotorula glutinis was evaluated using the cyclization inhibitor 2‐(4‐chlorophenylthio)‐triethylamine (Hayman et al. 1974), and the dehydrogenation inhibitors such as methyl‐heptanone, β‐ionone (Simpson et al. 1964) and DPA (Hayman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed in another strain of R. glutinis, 48-23T, in which the composition of carotenoids varied when different culture temperatures were applied. It was found that at 25°C the synthesized β-carotene, torulin and torulaihodin accounted for about 30% of the total carotenoids, respectively, whereas at 5°C, the proportion of β-carotene increased to 64%, by contrast the content of the other two carotenoids decreased significantly [35]. Buzzini and Martini [36] also reported that in R. glutinis the lower temperature (at 25°C) favored the synthesis of β-carotene and torulene whereas the higher temperature (30~35°C) is more suitable for the production of torularhodin.…”
Section: Optimization Approaches On Cultivation Conditions For the Prmentioning
confidence: 95%
“…glutinis, the carotenoids, was studied by Simpson et a1. [42]. It was found that carotenoid synthesis occurs mainly during the later stages of growth.…”
Section: Effect Of Carotenoid Pigments On the Endogenous Photosensitimentioning
confidence: 99%